Catalytic 1, 4‐Selective Hydrosilylation of Pyridines and Benzannulated Congeners1. Issue 38 (1st August 2013) - Königs, C. David F.; Klare, Hendrik F. T.; Oestreich, Martin
<x xml:space="preserve">Abstract</x> Radically different! The hydrosilylation of pyridines and quinolines is strictly 1, 4‐selective and likely involves an ionic one‐step rather than the established radical two‐step hydride transfer from a ruthenium(II) hydride complex onto the respective pyridinium and quinolinium ion intermediates (see scheme; ArF=3, 5‐(CF3)2C6H3). Even 4‐substituted substrates react highly regioselectively. Isoquinolines yield the 1, 2‐reduced heterocycles.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>